Effect of silver diamine fluoride on the microleakage of flowable resin composite and glass ionomer cement restorations to carious primary dentin: an-in vitro study - Sarah Osama; Amira Saad Badran; Basma Gamal Awad (BMC, 2024)
Abstract Background This study aimed to evaluate the effect of Silver Diamine Fluoride (SDF) on the microleakage of flowable resin composite (FRC) and resin-modified glass ionomer cement (GIC) restorations bound to carious primary dentin. Methods Forty-four extracted carious primary molars were allocated into four groups as follows (n = 11 teeth/group): Group I, Flowable resin composite (FRCa): SDF38% treatment + FRC, Group II, Flowable resin composite (FRCb): FRC without SDF treatment, Group III, Resin-modified glass ionomer cement (GICa): SDF38% treatment + GIC, Group IV, Resin-modified glass ionomer cement (GICb): GIC without SDF treatment. Specimens were subjected to thermo cycling at 500 cycles between 5 to 55 °C (dwell time of 60 seconds) in baths before being immersed for 24 h in a 1% toluidine blue solution. Microleakage testing was conducted for each specimen in two areas; occlusal and gingival. Specimens were evaluated under stereomicroscope at 4x magnification. Results were analyzed using Kruskal-Wallis test followed by pairwise comparisons utilizing Dunn's post hoc test at p ≤ 0.05. Results Insignificant differences between different groups (p = 0.49) were observed at the gingival walls area readings. The highest value was found in GICb (2.33 ± 0.52), while the lowest value was found in FRCa (1.71 ± 0.76). Insignificant differences between different groups (p = 0.982) were observed at the occlusal walls area readings. The highest value was found in FRCa (1.43 ± 0.98), while the lowest value was found in GICb (1.17 ± 1.33). Conclusion SDF does not adversely affect the microleakage of FRC and GIC restorations bound to carious primary dentin.